2014
DOI: 10.1177/0040517514559586
|View full text |Cite
|
Sign up to set email alerts
|

Infrared stealth property study of mesoporous carbon-aluminum doped zinc oxide coated cotton fabrics

Abstract: Low-emitting cotton fabric with low infrared emissivity near to 0.795 at the wavebands of 8–14 µm was prepared using mesoporous carbon-aluminum doped zinc oxide (C-AZO) coatings. The effects of binders, the content of C-AZO composites, coating thickness and roughness of fabrics on the infrared emissivity were investigated. Results showed that the emissivity firstly decreased, and then gradually reached a stable and lowest value as the content of C-AZO composites and coating thickness increased. The lowest infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 24 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Therefore, reducing the infrared emissivity of the target is an effective method for achieving infrared stealth. [8][9][10][11] In recent years, several lowinfrared-emissivity materials, such as semiconductors, [12,13] photonic crystals, [14,15] conducting polymers, [16,17] and organic/inorganic composites [18,19] have been developed. Among these materials, resin/metal composite coatings play an important role in infrared stealth owing to their low infrared emissivity, manufacturing convenience, excellent engineering performance, and low price.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reducing the infrared emissivity of the target is an effective method for achieving infrared stealth. [8][9][10][11] In recent years, several lowinfrared-emissivity materials, such as semiconductors, [12,13] photonic crystals, [14,15] conducting polymers, [16,17] and organic/inorganic composites [18,19] have been developed. Among these materials, resin/metal composite coatings play an important role in infrared stealth owing to their low infrared emissivity, manufacturing convenience, excellent engineering performance, and low price.…”
Section: Introductionmentioning
confidence: 99%
“…31 Wang et al coated cotton fabrics with mesoporous carbon-aluminum doped zinc oxide (C-AZO) and found that a coating layer of 40 wt% C-AZO and a thickness of 300 mm provided the fabrics with a far-infrared emissivity of 0.79. 32 According to these literature sources, most far-infrared emissive products are in the form of fabrics. Therefore, this study uses PP, WF, and far-infrared masterbatches to make wood plastic composites with far-infrared emissivity, the function of which can be further used in the construction industry, for health care equipment, and for daily applications for the human body.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, from the perspective of textile materials, there are mainly the following methods: developing new low emissivity fibers, [10][11][12][13] modifying existing fibers, [14][15][16] and designing special structures of fabrics. [17][18][19] Secondly, considering the exterior of textile materials, other materials with infrared camouflage function can be physically arranged on the surface of the fabric, such as low infrared emissivity coating, [20][21][22][23] heat insulation and temperature control coating. [24][25][26][27][28] In addition, with the continuous progress of multi-band detection technology and antiinfrared camouflage technology, multifunctional textile materials (for example, the material has infrared camouflage performance and visible light camouflage 29 / electromagnetic absorption [30][31][32] function at the same time) and infrared adaptive textile materials [33][34][35] (which can automatically adjust the infrared emissivity according to the infrared radiation characteristics of the environment) have also attracted much attention.…”
mentioning
confidence: 99%